Nonlinear Dynamics, Volume 1 Proceedings of the 34th IMAC, A Conference and Exposition on Structural Dynamics 2016 - Kerschen, Gaetan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Nonlinear Dynamics, Volume 1. Proceedings of the 34th IMAC, A Conference and Exposition on Dynamics of Multiphysical Systems: From Active Materials to Vibroacoustics, 2016, the fi rst volume of ten from the Conference, brings together contributions to this important area of research and engineering. Th e collection presents early fi ndings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: • Nonlinear Oscillations • Nonlinear Modal Analysis • Nonlinear System Identifi cation • Nonlinear Modeling & Simulation • Nonlinearity in Practice • Nonlinearity in Multi-Physics Systems • Nonlinear Modes and Modal Interactions.
1 Nonlinear Vibrations of a Beam with a Breathing Edge Crack Using Multiple Trial Functions -- 2 Enforcing Linear Dynamics Through the Addition of Nonlinearity -- 3 Experimental Analysis of a Softening-Hardening Nonlinear Oscillator Using Control-Based Continuation -- 4 Experimental Nonlinear Dynamics of Laminated Quasi-isotropic Thin Composite Plates -- 5 Experimental Identification of a Structure with Internal Resonance -- 6 Shock Response of an Antenna Structure Considering Geometric Nonlinearity -- 7 Investigation on Friction-excited Vibration of Flexibly Supported Shafting System -- 8 Resonant Analysis of Systems Equipped with Nonlinear Displacement-Dependent (NDD) Dampers -- 9 Performance Comparison Between a Nonlinear Energy Sink and a Linear Tuned Vibration Absorber for Broadband Control -- 10 Numerical Assessment of a Tunable Auxiliary Mass Damper Using a Friction Damper -- 11 Experimental and Numerical Investigation of the Nonlinear Bending-Torsion Coupling of a Clamped-Clamped Beam with Centre Masses -- 12 Tracking of Backbone Curves of Nonlinear Systems Using Phase-Locked-Loops -- 13 The Importance of Phase-Locking in Nonlinear Modal Interactions -- 14 A Study of the Modal Interaction Between Three Nonlinear Normal Modes Using a Backbone Curve Approach -- 15 Investigating Nonlinear Modal Energy Transfer in a Random Load Environment -- 16 Nonlinear Modal Testing Performed by Pulsed-air Jet Excitation System -- 17 EMA-FEA Correlation and Updating for Nonlinear Behaviour of an Automotive Heat-shield -- 18 Tutorial on Nonlinear System Identification -- 19 Higher-Order Frequency Response Functions for Hysteretic Systems -- 20 Model Upgrading T0 Augment Linear Model Capabilities Into Nonlinear Regions -- 21 Obtaining Nonlinear Frequency Responses from Broadband Testing -- 22 Experimental Study of Isolated Response Curves in a Two-degree-of-freedom Nonlinear System -- 23 Nonlinear Response of a Thin Panel in a Multi-Discipline Environment: Part I - Experimental Results -- 24 Nonlinear Dynamic Response Prediction of a Thin Panel in a Multi-Discipline Environment: Part II - Numerical Predictions -- 25 Stability Analysis of Curved Panels -- 26 Optimal Representation of a Varying Temperature Field for Coupling with a Structural Reduced Order Model -- 27 Basis Identification for Nonlinear Dynamical Systems Using Sparse Coding -- 28 Interaction Between Aerothermally Compliant Structures and Boundary Layer Transition -- 29 Simultaneous Vibration Isolation and Energy Harvesting: Simulation and Experiment -- 30 Nonlinear Dynamic Interaction In A Coupled Electro-Magneto-Mechanical System: Experimental Study -- 31 Hysteresis Identification Using Nonlinear State-Space Models -- 32 Nonholonomically Constrained Dynamics of Rolling Isolation Systems -- 33 Parameter Estimation on Nonlinear Systems Using Orthogonal and Algebraic Techniques -- 34 Online State and Parameter Estimation of a Nonlinear Gear Transmission System -- 35 Model Updating of a Nonlinear System: Gun Barrel of a Battle Tank -- 36 Experimental Passive Flutter Mitigation Using a Linear Tuned Vibration Absorber -- 37 Adaptive Harmonic Balance Analysis of Dry Friction Damped Systems -- 38 Dynamics of an MDOF Rotor Stator Contact System.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Solids; Materials -- Analysis; Multibody Systems and Mechanical Vibrations; Solid Mechanics; Characterization and Analytical Technique